Contact-induced disturbances in personal pronoun systems in the Chadic – Benue-Congo convergence zone in Central Nigeria - H. Ekkehard Wolff (Afrika und Übersee, 2020)
The paper looks at personal pronoun systems in languages of the convergence zone on both sides of the borderline between Benue-Congo and Chadic. Focus is on inventories and systems, meaning the overall interrelationship of pronoun shapes across the categories of person, number, grammatical gender and noun class (3rd person concord). The issues to be explored are (i) whether the personal pronoun systems as such provide any further indication towards the Sprachbund idea implied in Wolff & Gerhardt (1977), and (ii) whether one can identify some unusual features of or patterns within the systems, which are shared by languages on both sides of the line separating Benue-Congo and Chadic, and which are of such nature as to strengthen the hypothesis of a cross-genetic convergence zone. The answers provided are affirmative: In addition to cross-genetic borrowing of pronoun shapes, which is generally considered rare and/or at least remarkable, pronoun systems as such and across the convergence zone show at least two rather quirky disturbances of the expected pattern that can hardly be explained but by rather surprising instances of cross-language interference. These two kinds of disturbance within systems will be discussed under the headings of “category shifting” and “circumfix conjugational pattern” emergence. Given the present state of knowledge, the paper can only point out promising lines of detailed historical research: Any attempt to provide final answers would be premature at this stage.